Interview with Professor Etienne Durt: “50 years of a belgian in Peru: Etienne Durt a peruvian of heart and reason” - Delgado Estrada, Juan Manuel (2022)
This interview is a tribute to a character who came to Peru for love of a woman from Cuzco, who gave him a large family as he was used to in Belgium. Etienne Durt was present in these last 50 years of life in Peru that was transformed from the Agrarian Reform of the military government of General Velazco Alvarado, then the earthquake in Caraz and the reconstruction of the department of Huaraz in his case in the city of Chimbote . Then he was part of the state planning in the construction of the irrigation infrastructure that the country needed in that development model that the nationalist military sought from the INP (National Institute of Planning). As a good Belgian traveler, he was immersed in Peru that many Peruvians are unaware of today, Huancavelica in the midst of the internal armed conflict, Piura and its Sierra de Huancabamba, all through international development cooperation projects, which also led him to Bolivia to manage projects. Etienne Durt has not only the University of Louvain as his alma mater, but also UNALM, where the Belgian tradition was always present from its beginnings at the National School of Agriculture and Veterinary Medicine in 1902.